Implementasi Kebijakan Penganggaran Dana Desa Dalam Penanganan Pandemi Corona Virus Disease 19 Tahun Anggaran 2020 Di Kota Prabumulih - Kadarsyah, Fery; Idris, Umiyati; Zofir, Tasrif (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
In handling the Covid-19 pandemic in Prabumulih City, the Central Government which was followed up by the Government under it in this case the Village Government made a policy through the Village Community Development and Empowerment Program for Fiscal Year 2020 in Prabumulih City which included: (1) Use of village funds for handling and prevention of Corona Virus Disease 19, (2) the use of village funds for the Village Cash Work Intensive (PKTD); (3) Use of village funds for Direct Cash Assistance (BLT). The purpose of this study was to analyze the implementation of the Village Fund Budgeting Policy in Handling the Corona Virus Disease 19 Pandemic for the 2020 Fiscal Year in Prabumulih City. The problem in the research is the spread of the Corona Virus Disease 19 Pandemic that occurred in Prabumulih City in the range of March until now requires immediate treatment, but the Village Revenue and Expenditure Budget (APBDES) for 2020 has not accommodated activities and budgets for handling the Corona Virus Disease 19 Pandemic. This study shows that: overall the implementation of the Village Fund Budgeting Policy in Handling the Corona Virus Disease 19 Pandemic for Fiscal Year 2020 in Prabumulih City has been carried out in accordance with the Regulation of the Minister of Villages for Development of Disadvantaged Regions and Transmigration Number 6 of 2020 concerning Amendments to the Regulation of the Minister of Villages, Regional Development Disadvantaged and Transmigration Number 11 of 2019 concerning Priority for Use of Village Funds in 2020, Regulation of the Minister of Villages for Development of Disadvantaged Regions and Transmigration Number 7 of 2020 concerning the Second Amendment to Regulation of the Minister of Villages, Development of Disadvantaged Regions and Transmigration Nomo r 11 of 2019 concerning the Priority of the Use of Village Funds in 2020, Regulation of the Minister of Villages for Development of Disadvantaged Regions and Transmigration Number 14 of 2020 concerning the Third Amendment to the Regulation of the Minister of Villages, Development of Disadvantaged Regions and Transmigration Number 11 of 2019 concerning Priorities for the Use of Village Funds in 2020.